the door in the wall Marguerite De Angeli - Angeli, Marguerite De; Marguerite De Angeli (New York Doubleday dell publishing group Inc., 1949)
Set in 14th-century England, The Door in the Wall by Marguerite de Angeli is a Newbery Medal-winning historical novel about Robin de Bureford, a young nobleman who must find his own "door in the wall" after a sudden illness leaves his legs paralyzed. Robin learns soon enough what brother luke means. And when the great castle of lindsay is in danger, it is Robin, who cannot mount a hourse and ride to battle, who saves the towns people and discovers that there is more than one way to serve his king.
English